Application of Interpolated Loop Subdivision Mesh Deformation in Ecological Environment Animation. Issue 1 (March 2021) - Zeng, Shuzhen; Shi, Zhuo; Feng, Ye; Li, Mingrui; Wang, Meng; Shen, Jing
Abstract: In 3D computer vision processing, the introduction of deep learning into 3D research has always attracted much attention. In this paper, we introduce 3D mesh deformation into the animation of ecological environment research, adopt the 3D processing tool of Pytorch3D, and propose a 3D mesh deformation method based on the interpolation Loop subdivision. To prove the superiority of this algorithm, we compare the mesh deformation under the Loop subdivision and interpolation Loop subdivision. The experimental results show that after we adopted the interpolation Loop subdivision when the mesh deformation predicts the target mesh, the result of the deformation mesh is better than the Loop subdivision in terms of details. Thus, mesh deformation can be applied in the animation of the ecological environment, such as the "camouflage" of animals, which is of great significance to the animation or film related to the ecological environment.